The impact of hydrophilic emulsifiers on the physico-chemical properties, microstructure, water distribution and in vitro digestibility of proteins in fried snacks based on fish meat. Issue 10 (8th October 2019) - Nawaz, Asad; Xiong, Zhouyi; Xiong, Hanguo; Irshad, Sana; Chen, Lei; Wang, Peng-kai; Ahsan, Hafiz Muhammad; Walayat, Noman; Qamar, Sajid Hussain
Abstract : Hydrophillic emulsifiers strengthened the starch–protein interaction which resulted in improved physio-chemical properties of friend snacks based on fish meat. Abstract : The present study was aimed at investigating the effect of ionic and non-ionic emulsifiers at 3 different levels of 0.15, 0.30 and 0.45% per 100 g of flour on the physico-chemical properties, microstructure and water distribution of fish-meat based fried snacks. The results showed that the addition of distilled mono-glycerides (DMG) decreased the strength of the starch–protein network which resulted in increased expansion and decreased water holding capacity (WHC). The addition of diacetyl tartaric acid esters of mono-glycerides (DATEM) increased the WHC and the ordered structure between starch and proteins while oil uptake was decreased. Pasting properties such as breakdown, peak viscosity and pasting temperatures were increased with the addition of DATEM compared to DMG and the control indicating the strong interaction among DATEM, starch and proteins. Scanning electron microscopy (SEM) analysis showed that DATEM strengthened the starch–protein matrix and the dense and rigid microstructure with fewer voids while DMG increased the intercellular spaces between the molecules of starch and proteins. Low field nuclear magnetic resonance (LF-NMR) relaxometry analysis revealed that the amount of free water ( T 21 ) was decreased and that of bound water ( T 23 ) was increased in DATEM samples indicating the strong interaction between emulsifiers and macromolecules compared to the control and DMG. Moreover, protein in vitro digestibility was also increased with the addition of DATEM. The findings suggested that 0.30% DATEM can be used in snacks with improved physico-chemical and functional properties.